No supportive evidence for TIA1 gene mutations in a European cohort of ALS-FTD spectrum patients - Baradaran-Heravi, Yalda; Dillen, Lubina; Nguyen, Hung Phuoc; Van Mossevelde, Sara; Baets, Jonathan; De Jonghe, Peter; Engelborghs, Sebastiaan; De Deyn, Peter P; Vandenbulcke, Mathieu; Vandenberghe, Rik; Van Damme, Philip; Cras, Patrick; et al. (Neurobiology of aging, 2018)
We evaluated the genetic contribution of the T cell-restricted intracellular antigen-1 gene (TIA1) in a European cohort of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) patients. Exonic resequencing of TIA1 in 1120 patients (693 FTD, 341 ALS, 86 FTD-ALS) and 1039 controls identified in total 5 rare heterozygous missense variants, affecting the TIA1 low-complexity domain (LCD). Only 1 missense variant, p.Met290Thr, identified in a familial FTD patient with disease onset at 64 years, was absent from controls yet received a combined annotation-dependent depletion score of 11.42. By contrast, 3 of the 4 variants also detected in unaffected controls, p.Val294Glu, p.Gln318Arg, and p.Ala381Thr, had combined annotation-dependent depletion scores greater than 20. Our findings in a large European patient-control series indicate that variants in TIA1 are not a common cause of ALS and FTD. The observation of recurring TIA1 missense variants in unaffected individuals lead us to conclude that the exact genetic contribution of TIA1 to ALS and FTD pathogenesis remains to be further elucidated.
Keywords: Female; Amyotrophic Lateral Sclerosis; Mutation, Missense; missense mutace; Frontotemporal Dementia; mužské pohlaví; kohortové studie; Humans; frekvence genu; T-buněčný intracelulární antigen 1; Gene Frequency; běloši; frontotemporální demence; lidé; Cohort Studies; amyotrofická laterální skleróza; ženské pohlaví; White People; T-Cell Intracellular Antigen-1; Male